2020
DOI: 10.1186/s13071-020-04364-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of mitochondrial genes and predominance of Clade B in different head lice populations in the northwest of Iran

Abstract: Background The head louse, Pediculus humanus capitis, is the most important ectoparasite causing many health problems. Several linkages are presented for this parasite, each representing a particular geographical distribution, prevalence rate, vector competence, susceptibility to pediculicides, and infestation rate. Determining the genetic nature of these linkages is necessary to identify the population structure and also to develop and monitor control programmes against head lice. This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Clade A is distributed worldwide; clade D has only been reported in the Democratic Republic of Congo (Congo- Kinshasa ) , the Republic of Congo (Congo-Brazzaville), Zimbabwe and Ethiopia 9 , 19 , 21 . Clade B is observed in America, Western Europe, Australia, north Algeria, South Africa, Saudi Arabia, and Iran 20 , 22 25 . Clade F appears to be specific to South America, as it has not been reported elsewhere 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Clade A is distributed worldwide; clade D has only been reported in the Democratic Republic of Congo (Congo- Kinshasa ) , the Republic of Congo (Congo-Brazzaville), Zimbabwe and Ethiopia 9 , 19 , 21 . Clade B is observed in America, Western Europe, Australia, north Algeria, South Africa, Saudi Arabia, and Iran 20 , 22 25 . Clade F appears to be specific to South America, as it has not been reported elsewhere 19 .…”
Section: Introductionmentioning
confidence: 99%
“…To consider more about P. humanus Capitis, evaluating genetic diversity could be helpful. Different researchers showed that Cox1 DNA sequencing, as a mitochondrial gene, could reveal the genetic diversity of head lice (36). The results of our study showed that the most common type of lice among Iraqi students is clade D (44.87%).…”
Section: Genetic Diversity Evaluationsmentioning
confidence: 59%
“…The gDNA of the samples was extracted as described before [ 48 , 49 ]. In brief, the samples were stored at −70 °C for 1 h. The frozen bed bugs were then placed individually in 1.5-ml tubes and homogenized in 400 µl of a lysing buffer (100 mM of Tris HCl [pH 8.0], 0.5 mM of NaCl, 10 mM of EDTA, and 1% W/V SDS) with glass beads by the aid of an electric homogenizer.…”
Section: Methodsmentioning
confidence: 99%